Analysis of Utilization E-Commerceas as a Management Information System to Support Msme Performance - Rayyan Firdaus; Hairul Anissa; Klara Jesikarani Gajah (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
Technological advancements have encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt e-commerce as a platform for conducting business. Through e-commerce, business owners can not only display and market their products but also manage business data and make more effective managerial decisions. This article discusses the role of e-commerce as a management information system in improving MSME performance. Using a literature review method based on various scientific journals and academic books, the study found that e-commerce significantly enhances the efficiency of data management. In addition to expanding market reach and accelerating transaction processes, e-commerce also helps reduce operational costs. Furthermore, MSMEs can monitor sales data in real time and gain a better understanding of customer preferences and needs. In conclusion, utilizing e-commerce as a centralized data management system is an effective strategy for enabling MSMEs to remain competitive in the digital era.